An efficient metal-free and catalyst-free C–S/C–O bond-formation strategy: synthesis of pyrazole-conjugated thioamides and amides - Sharma, Shubham; Singh, Dharmender; Kumar, Sunit; Vaishali; Jamra, Rahul; Banyal, Naveen; Deepika; Malakar, Chandi C.; Singh, Virender (Beilstein Journal of Organic Chemistry, 2023)
An operationally simple and metal-free approach is described for the synthesis of pyrazole-tethered thioamide and amide conjugates. The thioamides were generated by employing a three-component reaction of diverse pyrazole C-3/4/5 carbaldehydes, secondary amines, and elemental sulfur in a single synthetic operation. The advantages of this developed protocol refer to the broad substrate scope, metal-free and easy to perform reaction conditions. Moreover, the pyrazole C-3/5-linked amide conjugates were also synthesized via an oxidative amination of pyrazole carbaldehydes and 2-aminopyridines using hydrogen peroxide as an oxidant.
Keywords: C–S/O bond formation; metal-free; oxidative amidation; pyrazole carbaldehydes; sulfur insertion; thioamides